CHM mutation spectrum and disease: An update at the time of human therapeutic trials. Issue 4 (19th February 2021) - Zeitz, Christina; Nassisi, Marco; Laurent‐Coriat, Caroline; Andrieu, Camille; Boyard, Fiona; Condroyer, Christel; Démontant, Vanessa; Antonio, Aline; Lancelot, Marie‐Elise; Frederiksen, Helen; Kloeckener‐Gruissem, Barbara; El‐Shamieh, Said; et al.
Abstract: Choroideremia is an X‐linked inherited retinal disorder (IRD) characterized by the degeneration of retinal pigment epithelium, photoreceptors, choriocapillaris and choroid affecting males with variable phenotypes in female carriers. Unlike other IRD, characterized by a large clinical and genetic heterogeneity, choroideremia shows a specific phenotype with causative mutations in only one gene, CHM . Ongoing gene replacement trials raise further interests in this disorder. We describe here the clinical and genetic data from a French cohort of 45 families, 25 of which carry novel variants, in the context of 822 previously reported choroideremia families. Most of the variants represent loss‐of‐function mutations with eleven families having large (i.e. ≥6 kb) genomic deletions, 18 small insertions, deletions or insertion deletions, six showing nonsense variants, eight splice site variants and two missense variants likely to affect splicing. Similarly, 822 previously published families carry mostly loss‐of‐function variants. Recurrent variants are observed worldwide, some of which linked to a common ancestor, others arisen independently in specific CHM regions prone to mutations. Since all exons of CHM may harbor variants, Sanger sequencing combined with quantitative polymerase chain reaction or multiplex ligation‐dependent probe amplification experiments are efficient to achieve the molecular diagnosis in patients with typical choroideremia features. Abstract : Choroideremia is an X‐linked inherited retinal disorder characterized by the degeneration of retinal pigment epithelium, photoreceptors, choriocapillaris, and choroid affecting males with variable phenotypes in female carriers. In the context of clinical trial in choroideremia, we conducted the necessary review of current knowledge of the disease and compared these with the clinical and genetic data found in our cohort of patients. A total of 338 distinct variants in 822 index patients with choroideremia have been reported so far spanning the entire gene.